Palladium-Catalyzed Synthesis of 9-(2-Cyclopentenyl) Guanine - Gultekin, Zeynep (Asian Journal of Chemistry, 2010)
The racemic synthesis of the 9-(2-cyclopentenyl) guanine (4) from 2-cyclopentenon was prepared in 4 steps with a good yield (43%) and excellent selectivity (N9-isomer). The syntheses were achieved in a convergent and direct manner via palladium(0) catalysed coupling between 2-amino-6-chloropurine and 2-cyclopentene-1-ethylcarbonate (2). Compounds 2–4 have been characterized by high resolution MS, 1H NMR and IR.